1997
DOI: 10.1161/01.cir.95.8.2068
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence for Impaired Nitric Oxide Synthesis in Patients With Peripheral Arterial Occlusive Disease

Abstract: In PAOD patients, there is a progressive reduction in urinary nitrate and cGMP excretion rates, which may be caused in part by accumulation of ADMA, an endogenous inhibitor of NO synthase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
256
5
15

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(287 citation statements)
references
References 36 publications
11
256
5
15
Order By: Relevance
“…This study is consistent with reports on increased circulating concentrations of ADMA in patients at risk or with vascular dysfunction or arteriosclerosis [7,10,13,25]. Serum concentrations of ADMA were approximately 20% higher in women with a history of GDM than in healthy women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is consistent with reports on increased circulating concentrations of ADMA in patients at risk or with vascular dysfunction or arteriosclerosis [7,10,13,25]. Serum concentrations of ADMA were approximately 20% higher in women with a history of GDM than in healthy women.…”
Section: Discussionsupporting
confidence: 92%
“…A decreased plasma L-arginine to ADMA ratio or increased ADMA concentrations has been described in hypercholesterolemia [6,7], hypertension [8,9], arterial occlusive disease [10], chronic renal failure [11], and preeclampsia [12]. It has been suggested that alteration of the L-arginine to ADMA ratio could affect the clinical course of arteriosclerosis, which has not been seen in patients with stable angina [13].…”
mentioning
confidence: 99%
“…13 In patients with peripheral arterial occlusive disease, they also reported that there was a significantly progressive increase in plasma ADMA concentrations related to the severity of peripheral arterial occlusive disease. 14 Miyazaki et al reported that, in patients without any symptoms of CAD or peripheral arterial occlusive disease, plasma ADMA concentrations correlated positively with the risk factors for atherosclerosis, including age, glucose intolerance, and mean arterial pressure, and also correlated well with carotid intima-media thickness, an index of early atherosclerosis. 15 Moreover, Böger et al recently demonstrated that, also by inhibition of NO formation, ADMA stimulated the secretion of monocyte chemotactic protein-1, increased endothelial superoxide radical formation, and potentiated monocyte adhesion, which suggested that ADMA might be a proatherogenic molecule.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It may compete with L-arginine as the substrate for NO synthase, increase oxidative stress by uncoupling of electron transport between NO synthase and L-arginine, and hence decrease both the production and availability of endothelium-derived NO. 18 Elevations of ADMA level have been observed in urine from hypertensive rats, 19 in the regenerating endothelium of balloon-injured vessels, 20 and in plasma from patients with hypercholesterolemia, 13 congestive heart failure, 21 peripheral arterial occlusive disease, 14 essential hypertension, 22 and hypertriglyceridemia. 23 These reports suggested that elevation of ADMA might be involved in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that by increasing plasma homocysteine concentrations using methionine infusion, FMD is impaired and this is associated with increased plasma ADMA [33]. Increased plasma concentrations of ADMA have also been described in a number of other conditions (Tables 1, 2) including diabetes mellitus, hypercholesterolaemia, hypertriglyceridaemia, hypertension, preeclampsia, stroke, peripheral vascular disease, congestive heart failure and acute coronary events [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. Of interest, increased ADMA concentrations have also been implicated in the pathogenesis of conditions not affecting the cardiovascular system such as schizophrenia although the exact mechanism has yet to be clarified [55].…”
Section: Adma and Endothelial Dysfunction In Disease Statesmentioning
confidence: 99%